The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1093/mnras/stx3129
|View full text |Cite
|
Sign up to set email alerts
|

Bars and spirals in tidal interactions with an ensemble of galaxy mass models

Abstract: We present simulations of the gaseous and stellar material in several different galaxy mass models under the influence of different tidal fly-bys to assess the changes in their bar and spiral morphology. Five different mass models are chosen to represent the variety of rotation curves seen in nature. We find a multitude of different spiral and bar structures can be created, with their properties dependent on the strength of the interaction. We calculate pattern speeds, spiral wind-up rates, bar lengths, and an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 141 publications
(201 reference statements)
5
66
1
Order By: Relevance
“…Our finding that the distribution of pitch angles (cot α) is more or less uniform among their observed galaxies, opens up the possibility that the pitch angles are actually evolving in time, as is found in the simulations (e.g. Grand et al 2013;Pettitt & Wadsley 2018;Mata-Chávez et al 2019). We note that in the modal density wave picture, this finding would need some other explanation.…”
Section: Discussionsupporting
confidence: 63%
“…Our finding that the distribution of pitch angles (cot α) is more or less uniform among their observed galaxies, opens up the possibility that the pitch angles are actually evolving in time, as is found in the simulations (e.g. Grand et al 2013;Pettitt & Wadsley 2018;Mata-Chávez et al 2019). We note that in the modal density wave picture, this finding would need some other explanation.…”
Section: Discussionsupporting
confidence: 63%
“…It appears that the bar pattern speed as well as R are affected by various parameters such galaxy rotation curve, gas fraction, halo shape, etc. (e.g., Athanassoula 2014;Pettitt & Wadsley 2018). For instance, Pettitt & Wadsley (2018) showed that the bar pattern speed depends rather critically on the shape of the rotation curve in such a way that bars under the "rising" rotation curve are slow, while the other rotation curves produce fast bars.…”
Section: Discussionmentioning
confidence: 99%
“…As a concrete example, Pettitt & Wadsley (2018) investigate the dependence of pattern speeds and wind-up rates on morphology in a sample of 5 model galaxies (designed to mimic M31, NGC4414, M33, M81 and the Milky Way). They were interested in investigating the impact of changing bar and disk properties, however, bulge mass also varies between their models, and there is a clear suggestion in their results that the wind-up rate is affected by bulge mass.…”
Section: Discussionmentioning
confidence: 99%